Inflammation markers in patients with psychotic disorder who have committed offenses and their relationship with criminal behavior - Yildiz, Sevler; Emir, Burcu Sirlier; Kilicaslan, Asli Kazgan; Kurt, Osman; Ugur, Kerim; Sehlikoglu, Seyma; Atmaca, Murad (Routledge Journals, Taylor & Francis Ltd, 2025)
The role of inflammation in the etiology of psychotic disorders (PD) is well-established. This study aimed to identify inflammation parameters in patients diagnosed with PD, assess their potential as biomarkers, and examine their relationship with criminal behavior. This retrospective study comprised three groups: 530 patients diagnosed with PD who had committed crimes (offenders with PD), 530 patients with PD who had not committed crimes (non-offenders with PD), and 530 healthy controls, totaling 1,590 participants. Routine hematological tests were used to measure neutrophil, lymphocyte, monocyte, and platelet counts, high-density lipoprotein (HDL), systemic inflammatory response index (SIRI), systemic immune-inflammatory index (SII), and neutrophil/HDL (NHR), lymphocyte/HDL, platelet/HDL (PHR), and monocyte/HDL (MHR) ratios. Offenders with PD exhibited significantly higher levels of SII, SIRI, PHR, NHR, LHR, neutrophils, and monocytes compared to non-offenders with PD and healthy controls (p < 0.001). The criminal group had lower HDL and lymphocyte levels than the remaining two groups (p < 0.001). Among those treated in forensic psychiatry units, patients with two or more treatments showed significantly higher SIRI values compared to those with only one treatment (p = 0.045). Non-offenders with PD had higher platelet values than the remaining two groups (p < 0.001). This study underscores the role of systemic inflammation in the pathophysiology of psychotic disorders through a comparison of patients who have and have not committed crimes, highlighting the relationship between inflammation and lipid metabolism. Further research is required to clarify these findings.
Keywords: Psychotic disorder; SIRI; SII; inflammation; HDL; hemogram